Uncovering the chain of corruption: A Case Study in Bangladesh - Hossan, Md. Alomgir; Abdur Rohim Sourav; Jakirul Islam (DIROSAT: Journal of Education, Social Sciences & Humanities, 2024)
Government officials are responsible to the people because they are paid for their services by the fund of the country which is collected from people. They got extra facilities as the government officials but people see them as the oppressors while taking public services. Their offensive behavior hurts the common people who do not have extra money paid for services. This study attempts to make the people aware, conscious, responsible, accountable, and transparent to government officials. The study titled "Uncovering the Chain of Corruption: A Case Study in Bangladesh" delves into the intricate web of corruption within Bangladesh, highlighting systemic issues and identifying key actors involved. This research adopts a mixed-methods approach, utilizing both qualitative interviews and quantitative data analysis, to provide a comprehensive examination of corruption at various levels of governance and society. Findings reveal that corruption in Bangladesh is deeply entrenched, facilitated by a nexus of political patronage, bureaucratic inefficiencies, and socio-economic disparities. The case study uncovers how corruption manifests in public procurement, law enforcement, and the judiciary, perpetuating a cycle of impunity and public mistrust which is conducted at Bangladesh Road Transport Authority in Rajshahi Zone. Furthermore, the study explores the socio-cultural dimensions that normalize corrupt practices and examines the role of international aid and non-governmental organizations in both exacerbating and combating corruption. Recommendations emphasize the need for robust legal frameworks, greater transparency, and public accountability mechanisms, alongside fostering a culture of integrity and ethical governance. This study contributes to the broader discourse on anti-corruption strategies, offering insights that are crucial for policymakers, stakeholders, and scholars aiming to address corruption in developing countries.